A graphene-like nanoribbon for efficient bifunctional electrocatalysts. Issue 47 (20th October 2021) - Peng, Hongliang; Duan, Diancheng; Liu, Siyan; Liu, Jiaxi; Sun, Lixian; Huang, Pengru; Shao, Chunfeng; Zhang, Kexiang; Zhang, Huanzhi; Xue, Xiaogang; Xu, Fen; Zou, Yongjin; et al.
Abstract : A graphene-like nanoribbon has been synthesized by a one-step heat treatment method. And which have excellent bifunctional oxygen electrocatalysis due to their efficient synergistic effect between Fe, Co, N and F, and full exposure of active sites. Abstract : Graphene nanoribbons (GNRs) are conducive to full exposure of catalyst sites, which can be used to synthesize highly efficient electrocatalysts. However, the design of stable and efficient GNR catalysts remains a great challenge. Herein, a novel iron and cobalt co-doped carbon-based catalyst (C-MP-FeCo) with a GNR structure has been developed by a facile and one-step heat-treatment method. C-MP-FeCo is an excellent bifunctional electrocatalyst for low potential difference Δ E between the oxygen-evolution reaction and oxygen-reduction reaction (Δ E C-MP-FeCo = 0.70 V vs. Δ E (Pt/C+RuO2 ) = 0.765 V). The maximum power reached 331 mW cm −2 at 0.97 V for a Zn–air battery derived from the C-MP-FeCo catalyst, and with the Pt/C + RuO2 catalyst it was only 249 mW cm −2 at 0.89 V; also, better discharge performance, voltage efficiency and durability were delivered by the former catalyst. Our findings show that the main methods of increasing electrocatalytic activity are (1) forming GNRs and exposing active sites, and (2) exploiting the synergistic effects of Fe, Co, N, and F.